RH refining furnace bottom ramming material with low-grade magnesite tailings as aggregate
By using low-grade magnesite tailings and waste magnesium carbon bricks and other aggregates, combined with silicon micropowder, alumina differential, zirconia differential and silicon sol, a new RH refining furnace bottom ramming material is formed, which solves the problems of large resource consumption and serious environmental pollution in the existing technology, and achieves high-performance and environmentally friendly ramming material.
Patent Information
- Application Number
- CN202411868505.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
When the oxidation atmosphere coexists with strong alkali oxides in the existing RH refining furnace bottom ramming material, the chromium will be transformed into toxic Cr6+, and the resource consumption is high and the environmental pollution is serious.
Low-grade magnesite tailings and waste magnesium carbon bricks are used as aggregates, and silicon micropowder, alumina differential and zirconia differential, and silica sol as binding agents are added to form a new RH refining furnace bottom ramming material.
The ramming material has high volume density, low porosity, excellent chemical mineral structure, physical properties and thermal shock stability. It not only saves mineral resources, but also solves the emission problems of tailings and waste bricks, and is environmentally friendly.
Smart Images

Figure BDA0005195131180000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of unshaped refractory materials, in particular to a ramming mass for a RH refining furnace bottom using low-grade magnesite tailings as aggregate. Background Art
[0002] The bottom of the RH refining furnace is composed of several circulation tubes, among which the four sides of the circular circulation tubes are in contact with the shaped furnace bottom electrofused and bonded magnesia-chrome bricks. The large gaps between them are filled with ramming materials, which are compacted by tamping machines to form a closed furnace bottom structure. The ramming materials commonly used in the RH refining furnace bottom are magnesia-chrome ramming materials, in which chromium is mainly Cr 2 O 3 In the form of Cr 2 O 3 In an oxidizing atmosphere with strong alkaline oxides such as Na 2 O.K 2 In the case of coexistence of O or CaO, Cr 3+ Can be converted into Cr 6 + ,Cr 6+ It is easy to leach, highly toxic, and pollutes the environment.
[0003] At present, there are many literature reports on RH refining furnace bottom ramming materials. For example, the Chinese patent with authorization announcement number CN104177102B (reference document 1) discloses a RH refining furnace bottom ramming material, which is composed of dry material and an added binder. The dry material is composed of the following components by weight percentage: 70-80% fused magnesia, 5-10% magnesia-alumina spinel, Al 2 O 3 Micro powder 1-5% and metal powder 1-10%, among which fused magnesia and magnesia-alumina spinel are refractory aggregates, Al 2 O 3The micro powder and metal powder are refractory powders, the binder is an inorganic salt, and the amount of the binder added is 1-5% of the weight of the dry material. The patent discloses the use of fused magnesia and magnesia-alumina spinel ramming materials instead of magnesia-chromium ramming materials. The Chinese patent with authorization announcement number CN104072166 B (reference document 2) discloses a ramming material for the bottom of an electric furnace, the formula of which contains 20-40% of fused magnesia or high-purity magnesia aggregates of 5-3mm, 10-25% of fused magnesia or high-purity magnesia aggregates of 3-1mm, 15-25% of fused magnesia or high-purity magnesia aggregates of 1-0mm, and 20-30% of fused magnesia fine powder or high-purity magnesia fine powder <88μm; in addition, brine accounting for 4-6% of the total weight of the above raw materials is added as a binder. The patent also discloses a ramming material with fused magnesia or high-purity magnesia as aggregate. With the vigorous development of the steel industry, the consumption of mineral resources is increasing, and resources are becoming increasingly scarce. It is urgent to develop a high-quality and low-cost ramming material. In addition, with the rapid development of electric arc furnace refining technology, the performance requirements for the ramming material of the electric furnace bottom are also getting higher and higher. Summary of the invention
[0004] In order to overcome the defects of the prior art, the technical problem solved by the present invention is to provide a ramming mass for the bottom of an RH refining furnace using low-grade magnesite tailings as aggregate, and the ramming mass using low-grade magnesite tailings and waste magnesia-carbon bricks that cannot be used to prepare magnesia materials as aggregates. The ramming mass has a complete bonding phase, a large volume density, a small apparent porosity, high compressive and flexural strength, and has an excellent chemical mineral structure, physical properties and thermal shock stability. It not only saves mineral resources, but also solves the problem of the discharge of magnesite tailings and waste magnesia-carbon bricks after mineral processing, and is energy-saving and environmentally friendly.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A ramming material for the bottom of an RH refining furnace using low-grade magnesite tailings as aggregate, comprising aggregate and an external binder, characterized in that the aggregate comprises the following components by weight percentage:
[0007] Low-grade magnesite tailings 60-65wt%;
[0008] Waste magnesia carbon bricks 20-25wt%;
[0009] Silicon powder 5-10wt%;
[0010] Alumina fraction 3-5wt%;
[0011] Zirconia differential 3-5wt%;
[0012] The binder is silica sol, which accounts for 4-6wt% of the aggregate by weight.
[0013] Furthermore, the particle size distribution of the low-grade magnesite tailings is as follows:
[0014] 2.5mm<particle size≤5mm 25~30wt%;
[0015] 0.75mm<particle size≤2.5mm 30~35wt%;
[0016] 220 mesh<particle size≤0.75mm 25~30wt%;
[0017] Particle size = 220 mesh 10-15wt%.
[0018] Furthermore, the waste magnesia carbon bricks have a MgO content of ≥85wt%, a C content of ≤10wt%, and a particle size distribution as follows:
[0019] 2.5mm<particle size≤5mm 25~30wt%;
[0020] 0.75mm<particle size≤2.5mm 30~35wt%;
[0021] 220 mesh<particle size≤0.75mm 25~30wt%;
[0022] Particle size = 220 mesh 10-15wt%.
[0023] Furthermore, the SiO 2 Content ≥95%, particle size is 280 mesh.
[0024] Furthermore, the Al2O3 differential 2 O 3 Content ≥93%, particle size 300 mesh.
[0025] Furthermore, the particle size of the zirconium oxide fraction is 320 meshes.
[0026] Preferably, a RH refining furnace bottom ramming material using low-grade magnesite tailings as aggregate is composed of aggregate and an added binder, wherein the aggregate includes the following components by weight percentage:
[0027] Low-grade magnesite tailings 62.5wt%;
[0028] Waste magnesia carbon bricks 22.5wt%;
[0029] Silica powder 7wt%;
[0030] Alumina differential 4wt%;
[0031] Zirconia differential 4wt%;
[0032] The binder is silica sol, which accounts for 5wt% of the aggregate by weight.
[0033] Preferably, the particle size distribution of the low-grade magnesite tailings is as follows:
[0034] 2.5mm<particle size≤5mm 27.5wt%;
[0035] 0.75mm<particle size≤2.5mm 32.5wt%;
[0036] 220 mesh<particle size≤0.75mm 27.5wt%;
[0037] Particle size = 220 mesh 12.5wt%.
[0038] Preferably, the waste magnesia carbon bricks have a MgO content of ≥85wt%, a C content of ≤10wt%, and a particle size distribution as follows:
[0039] 2.5mm<particle size≤5mm 27.5wt%;
[0040] 0.75mm<particle size≤2.5mm 32.5wt%;
[0041] 220 mesh<particle size≤0.75mm 27.5wt%;
[0042] Particle size = 220 mesh 12.5wt%.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] 1) The ramming material of the present invention uses low-grade magnesia tailings and waste magnesia carbon bricks instead of fused magnesia sand, magnesia-alumina spinel or high-purity magnesia sand as aggregate, so that low-grade magnesia tailings and waste magnesia carbon bricks that cannot be used to prepare magnesia materials are effectively recycled, which not only saves mineral resources, but also solves the problem of discharge of magnesia tailings and waste magnesia carbon bricks after beneficiation, and is energy-saving and environmentally friendly;
[0045] 2) The ramming material of the present invention introduces a zirconium oxide modifier, which can significantly improve the bulk density, relative density, room temperature compressive strength, and thermal shock resistance of the ramming material, so that various performance indicators of the RH refining furnace bottom after ramming are optimized until they reach the optimum;
[0046] 3) The silicon powder and alumina powder in the ramming material of the present invention can fill the pores and increase the density and strength of the material. 2 ) and alumina powder (Al 2 O 3 ) When the micro powder coexists, it is easier to generate mullite phase, which can fill the pores in the material, increase the density of the material, and thus improve the high temperature strength performance of the material. In addition, mullite has good thermal shock stability, so it can improve the thermal shock stability of the material;
[0047] 4) The ramming material of the present invention uses low-grade magnesite tailings and waste magnesia-carbon bricks that cannot be used to prepare magnesia materials as main materials and adds a certain amount of admixtures. The combined phase is complete, the bulk density is large, the apparent porosity is small, about 14-15%, the compressive strength and flexural strength are high, and it has excellent chemical mineral structure, physical properties and thermal shock stability. DETAILED DESCRIPTION
[0048] The technical solution of the present invention will be further clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] The raw materials used in the examples of the present invention, unless otherwise specified, are all commercially available conventional raw materials; the process methods used in the examples, unless otherwise specified, are all conventional methods in the art.
[0050] The low-grade magnesite tailings used in the embodiment of the present invention are magnesite tailings selected by a ore dressing plant in Haicheng, Liaoning Province, and the chemical composition thereof is MgO 35-41%, CaO 8.66-15.21%, SiO 2 2.11~6.22%,Al 2 O 3 0.52~1.28%,Fe 2 O 3 2.32~3.82%, the remainder is trace impurities.
[0051] [Example 1]:
[0052] A ramming material for the bottom of an RH refining furnace using low-grade magnesite tailings as aggregates, comprising aggregates and an external binder, wherein the aggregates include the following components by weight percentage:
[0053] Low-grade magnesite tailings 62.5wt%;
[0054] Waste magnesia carbon bricks 22.5wt%;
[0055] Silica powder 7wt%;
[0056] Alumina differential 4wt%;
[0057] Zirconia differential 4wt%;
[0058] The binder is silica sol, which accounts for 5wt% of the aggregate by weight.
[0059] Furthermore, the particle size distribution of the low-grade magnesite tailings is as follows:
[0060] 2.5mm<particle size≤5mm 27.5wt%;
[0061] 0.75mm<particle size≤2.5mm 32.5wt%;
[0062] 220 mesh<particle size≤0.75mm 27.5wt%;
[0063] Particle size = 220 mesh 12.5wt%.
[0064] Furthermore, the waste magnesia carbon bricks have a MgO content of ≥85wt%, a C content of ≤10wt%, and a particle size distribution as follows:
[0065] 2.5mm<particle size≤5mm 27.5wt%;
[0066] 0.75mm<particle size≤2.5mm 32.5wt%;
[0067] 220 mesh<particle size≤0.75mm 27.5wt%;
[0068] Particle size = 220 mesh 12.5wt%.
[0069] Furthermore, the SiO 2 Content ≥95%, particle size is 280 mesh.
[0070] Furthermore, the Al2O3 differential 2 O 3 Content ≥93%, particle size 300 mesh.
[0071] Furthermore, the particle size of the zirconium oxide fraction is 320 meshes.
[0072] In this embodiment, a zirconium oxide modifier is introduced to significantly improve the bulk density, relative density, room temperature compressive strength, and thermal shock resistance of the brick.
[0073] In this embodiment, the silicon powder and alumina powder in the components can fill the pores, increase the density and strength of the material, and in addition, the silicon powder (SiO 2 ) and alumina powder (Al 2 O 3 ) When micro powders coexist, mullite phase is more likely to be generated. Mullite phase can fill the pores in the material to increase the density of the material, thereby improving the high-temperature strength performance of the material. Mullite has good thermal shock stability, so it can improve the thermal shock stability of the material.
[0074] [Example 2]:
[0075] A ramming material for the bottom of an RH refining furnace using low-grade magnesite tailings as aggregates, comprising aggregates and an external binder, wherein the aggregates include the following components by weight percentage:
[0076] Low-grade magnesite tailings 65wt%;
[0077] Waste magnesia carbon bricks 20wt%;
[0078] Silica powder 9wt%;
[0079] Alumina differential 3wt%;
[0080] Zirconia differential 3wt%;
[0081] The binder is silica sol, which accounts for 6wt% of the aggregate by weight.
[0082] Furthermore, the particle size distribution of the low-grade magnesite tailings is as follows:
[0083] 2.5mm<particle size≤5mm 30wt%;
[0084] 0.75mm<particle size≤2.5mm 35wt%;
[0085] 220 mesh<particle size≤0.75mm 25wt%;
[0086] Particle size = 220 mesh 10wt%.
[0087] Furthermore, the waste magnesia carbon bricks have a MgO content of ≥85wt%, a C content of ≤10wt%, and a particle size distribution as follows:
[0088] 2.5mm<particle size≤5mm 25wt%;
[0089] 0.75mm<particle size≤2.5mm 35wt%;
[0090] 220 mesh<particle size≤0.75mm 30wt%;
[0091] Particle size = 220 mesh 10wt%.
[0092] The particle sizes of silicon micropowder, alumina micropowder and zirconia micropowder are the same as those in Example 1.
[0093] [Example 3]
[0094] A ramming material for the bottom of an RH refining furnace using low-grade magnesite tailings as aggregates, comprising aggregates and an external binder, wherein the aggregates include the following components by weight percentage:
[0095] Low-grade magnesite tailings 60wt%;
[0096] Waste magnesia carbon bricks 25wt%;
[0097] Silica powder 5wt%;
[0098] Alumina differential 5wt%;
[0099] Zirconia differential 5wt%;
[0100] The binder is silica sol, which accounts for 4wt% of the aggregate by weight.
[0101] Furthermore, the particle size distribution of the low-grade magnesite tailings is as follows:
[0102] 2.5mm<particle size≤5mm 25wt%;
[0103] 0.75mm<particle size≤2.5mm 30wt%;
[0104] 220 mesh<particle size≤0.75mm 30wt%;
[0105] Particle size = 220 mesh 15wt%.
[0106] Furthermore, the waste magnesia carbon bricks have a MgO content of ≥85wt%, a C content of ≤10wt%, and a particle size distribution as follows:
[0107] 2.5mm<particle size≤5mm 30wt%;
[0108] 0.75mm<particle size≤2.5mm 30wt%;
[0109] 220 mesh<particle size≤0.75mm 25wt%;
[0110] Particle size = 220 mesh 15wt%.
[0111] The particle sizes of silicon micropowder, alumina micropowder and zirconia micropowder are the same as those in Example 1.
[0112] According to conventional inspection methods such as GB / T 7321-2017 "Preparation method for samples of shaped refractory products", GB / T 2997-2015 "Test method for bulk density, apparent porosity and true porosity of dense shaped refractory products", GB / T 5072-2023 "Test method for compressive strength of refractory materials at room temperature", GB / T3001-2017 "Test method for flexural strength of refractory materials at room temperature", and GB / T5988-2022 "Test method for permanent linear change of refractory materials upon heating", the performance tests were carried out on the castable samples prepared by using the raw materials of Examples 1 to 3, and the test results are shown in Table 1.
[0113] Table 1
[0114]
[0115] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A ramming material for the bottom of an RH refining furnace using low-grade magnesite tailings as aggregate, which is composed of aggregate and an added binder, characterized in that: The aggregate comprises the following components by weight percentage: Low-grade magnesite tailings 60-65wt%; Waste magnesia carbon bricks 20-25wt%; Silicon powder 5-10wt%; Alumina fraction 3-5wt%; Zirconia differential 3-5wt%; The binder is silica sol, which accounts for 4-6wt% of the aggregate by weight.
2. The RH refining furnace bottom ramming material using low-grade magnesite tailings as aggregate according to claim 1, characterized in that: The particle size distribution of the low-grade magnesite tailings is as follows: 2.5mm<particle size≤5mm 25~30wt%; 0.75mm<particle size≤2.5mm 30~35wt%; 220 mesh<particle size≤0.75mm 25~30wt%; Particle size = 220 mesh 10-15wt%.
3. The RH refining furnace bottom ramming material using low-grade magnesite tailings as aggregate according to claim 1, characterized in that: The waste magnesia carbon brick has a MgO content of ≥85wt%, a C content of ≤10wt%, and a particle size distribution as follows: 2.5mm<particle size≤5mm 25~30wt%; 0.75mm<particle size≤2.5mm 30~35wt%; 220 mesh<particle size≤0.75mm 25~30wt%; Particle size = 220 mesh 10-15wt%.
4. The RH refining furnace bottom ramming material using low-grade magnesite tailings as aggregate according to claim 1, characterized in that: The SiO2 content of the silicon micropowder is ≥95%, and the particle size is 280 meshes.
5. The RH refining furnace bottom ramming material using low-grade magnesite tailings as aggregate according to claim 1, characterized in that: The Al2O3 content of the alumina differential is ≥93%, and the particle size is 300 meshes.
6. The RH refining furnace bottom ramming material using low-grade magnesite tailings as aggregate according to claim 1, characterized in that: The particle size of the zirconium oxide fraction is 320 mesh.
7. The RH refining furnace bottom ramming material using low-grade magnesite tailings as aggregate according to claim 1, characterized in that: The aggregate comprises the following components by weight percentage: Low-grade magnesite tailings 62.5wt%; Waste magnesia carbon bricks 22.5wt%; Silica powder 7wt%; Alumina differential 4wt%; Zirconia differential 4wt%.
8. The RH refining furnace bottom ramming material using low-grade magnesite tailings as aggregate according to claim 1, characterized in that: The binder is silica sol, which accounts for 5wt% of the aggregate by weight.
9. The RH refining furnace bottom ramming material using low-grade magnesite tailings as aggregate according to claim 1 or 7, characterized in that: The particle size distribution of the low-grade magnesite tailings and waste magnesia-carbon bricks is as follows: 2.5mm<particle size≤5mm 27.5wt%; 0.75mm<particle size≤2.5mm 32.5wt%; 220 mesh<particle size≤0.75mm 27.5wt%; Particle size = 220 mesh 12.5wt%.
Citation Information
Patent Citations
Electric furnace bottom ramming material
CN104072166B
A kind of ramming material at the bottom of rh refining furnace
CN104177102B